Audiovisual crossmodal cuing effects in front and rear space - Lee, Jae; Spence, Charles (Frontiers in Psychology, 2015)
The participants in the present study had to make speeded elevation discrimination responses to visual targets presented to the left or right of central fixation, following the presentation of a task-irrelevant auditory cue on either the same or opposite side. In Experiment 1, when the cues were presented from in front of the participants (from the same azimuthal positions as the visual targets), the standard crossmodal exogenous spatial cuing effect was observed: That is, the participants responded significantly faster in the elevation discrimination task for visual targets when both auditory cues and visual targets were presented on the same side. Experiment 2, in which the auditory cues were either presented from the front or rear, replicated the exogenous spatial cuing effect for frontal visual targets from both front and rear cue-space, with participants responding significantly more rapidly to front targets when cues were presented on the same side, no matter whether the cues were presented from the front or rear. Importantly, the results of Experiment 3 showed that the participants had little difficulty in correctly discriminating the location from which the sounds were presented. Thus, taken together, the results of the three experiments reported here demonstrate that the exact co-location of auditory cues and visual targets is not necessary to attract spatial attention. Implications for the design of real-world warning signals are discussed.